Enhancing Reading Abilities in Students with Learning Disabilities Through Cooperative Integrated Reading and Composition Based on Team-Based Learning - Rusdiana, Rusdiana; Ishartiwi, Ishartiwi (Papanda Publisher, 2025)
Students with learning disabilities frequently struggle with reading acquisition, requiring specialized interventions that address their unique learning needs. This study investigated the effectiveness of integrating Cooperative Integrated Reading and Composition (CIRC) with Team-Based Learning (TBL) principles to improve reading abilities among fourth-grade students with learning disabilities. A classroom action research design was employed using the Kemmis and McTaggart cyclical model across two intervention cycles. Four fourth-grade students with identified reading difficulties participated in the study conducted at SD Negeri 007 Muara Bengkal, Indonesia. The intervention progressed from simple syllable patterns (KVKV) in Cycle I to complex patterns (KKVV and KVKK) in Cycle II. Data collection utilized validated reading assessment instruments, systematic observation protocols, and documentation. Assessment components included word reading, writing abilities, sentence construction, storytelling, and learning engagement, analyzed through descriptive statistics and percentage calculations. All participants demonstrated substantial improvements from pre-intervention to post-intervention assessments. The class average increased from 48.56% in Cycle I to 73.88% in Cycle II, representing a 25.32 percentage point improvement. Students with the most severe initial difficulties achieved the greatest gains, with individual improvements ranging from 4.75% to 34.25%. All participants progressed from below-standard categories to adequate or good performance levels. Observational data revealed enhanced engagement, collaborative behaviors, and sustained task persistence throughout the intervention. The CIRC-TBL integration effectively addressed reading difficulties while promoting collaborative learning skills. The intervention's success supports theoretical frameworks emphasizing cooperative learning and multisensory instruction for students with learning disabilities. Findings demonstrate that structured collaborative approaches can serve as effective alternatives to traditional remediation, enabling inclusive classroom practices that benefit diverse learners.